PENGARUH TANGGUNG JAWAB MORAL, KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN KUALITAS PELAYANAN PADA KEPATUHAN PELAPORAN WAJIB PAJAK BADAN - indriyani, putu arika; Sukartha, I Made (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of moral responsibility, awareness of taxpayers, tax penalties and quality of service on taxpayer compliance reporting agency in KPP Pratama Badung Utara. Retrieval and sampling in this study using accidental sampling technique. Respondents in this study is 98 Taxpayer using minimal criteria taxation or accounting staff, working a minimum of 2 years and never fill their annual tax return. Multiple linear regression analysis were used in this research show moral responsibility, awareness of taxpayers, tax penalties and service quality positive and significant impact on taxpayer compliance reporting entity in KPP Pratama Badung Utara.
Keywords: moral, awareness, Penalties, Service Quality and Compliance Reporting Taxpayer